Pengambangan Maharah Istima’ dengan PPTQ di Kelas IX SMP Plus Bustanul Ma’arif Jember - Ahmad Mizan Rosyadi Abdul Jalil Mannan; Mahmud Mau Robbi (An-Nuqthah, 2022)
In learning maharah istima', it is very necessary to have a good basis for capturing and digesting the language itself, especially Arabic, and the first step in introducing Arabic is to introduce vocabulary (mufradat) first, as the main factor for success in learning Arabic. This research aimed to describe the implementation of PPTQ learning in 9th grade students in junior high school plus Bustanul Ma'arif Jember. This study used a qualitative approach with data collection through observation and documentation. The results of the research showed that PPTQ learning has more influence on the maharah istima' learning process with good grades in listening to sentences and creativity in translating with an average of 88.4% very capable, 8% able, and 4% less able. This showed that the majority of students were able to listen and translate sentences well. PPTQ can be used as a supporting material for teaching and learning Arabic to hone the ability of maharah istima' and translate.